(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research intends to provide an academic viewpoint on the value of studying "Greek Mythology" in a historical context by tracing its roots as a primary philosophy. Myths are complex because they contain historical information. The study subject focuses on the success of the Greek epics poet "Homer," who mixed mythology with history in a philosophical and literary framework. Both epics incorporated rhetorical visuals, graphic arts, supernatural, and philosophical elements. The research relies on a historical, descriptive technique, examining important documents, books, papers, and research. According to the study, the Iliad and the Odyssey reveal the influence of myth on Greek thinking and ideology. The Iliad reveals "Trojan War" mysteries and facts. Homer’s descriptions of events and episodes are consistent with those of Greek historians, especially Thucydides. The research made several important recommendations, including the need to include in university curricula topics on the philosophy of history that provides for eastern and western mythological symbols because of their importance as part of the cultural heritage of peoples that must be revived in all countries, and the need to hold seminars and scientific conferences to shed light on the importance of the symbols.